Teaching-Learning Challenges Facing Students of English in the Preparatory Year at the Taif University, Kingdom of Saudi Arabia - Tawalbeh, Thaer Issa (EDUCARE, 2014)
ABSTRACT: The present study aimed to investigate the teaching-learning challenges students face in the Preparatory Year Program (PYP) at Taif University from instructors and students perspectives. The first two questions were concerned with the instructorsâ and studentsâ extent of agreement on the challenges students face while learning English in the preparatory year at Taif University from studentsâ and instructorsâ points of view. The third question tried to answer whether there were any statistically significant differences at (a = 0.05) between instructorsâ and studentsâ responses due to the five domains of teaching-learning challenges. Descriptive statistics were used to analyze the data related to the first two questions, and Independent t-test was used to answer the third question. The findings of the first question showed that the fifth and the first domains include most of the teaching-learning challenges facing Taif University students in the Preparatory Year Program from the instructorsâ point of view. The results of the second question indicated that with the exception of the third domain, all the other domains represent teaching-learning challenges facing students from their own points of view. In addition, the results of the first two questions showed an agreement between instructors and students in terms of ranking the fifth and the first domains as having most of the teaching-learning challenges facing students. As for the third question, the findings showed that there were statistically significant differences at (a = 0.05) between instructorsâ and studentsâ views due to the five domains of the teaching-learning challenges. These findings could be due to the fact that instructors and students are two heterogeneous groups having different mentalities, belonging to different age groups, and educational and cultural backgrounds. KEY WORDS: Instructorsâ perceptions, studentsâ perceptions, teaching-learning challenges, Taif University students, learning EFL, and preparatory year.About the Author: Dr. Thaer Issa Tawalbeh is a Lecturer at the Testing Unit, English Language Center TU (Taif University) in Kingdom of Saudi Arabia. For academic purposes, the author can be contacted via his e-mail address at: ansathaer@hotmail.comHow to cite this article? Tawalbeh, Thaer Issa. (2014). âTeaching-Learning Challenges Facing Students of English in the Preparatory Year at the Taif University, Kingdom of Saudi Arabiaâ in EDUCARE: International Journal for Educational Studies, Vol.6(2) February, pp.145-160. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 15, 2013); Revised (January 18, 2014); and Published (February 17, 2014).Â  Â